Nitrogen application enhances yield, yield-attributes, and physiological characteristics of dryland wheat/maize under strip intercropping - Hussain, Sadam; Naseer, Muhammad Asad; Guo, Ru; Han, Fei; Ali, Basharat; Chen, Xiaoli; Ren, Xiaolong; Alamri, Saud (Frontiers in Plant Science, 2023)
Intercropping has been acknowledged as a sustainable practice for enhancing crop productivity and water use efficiency under rainfed conditions. However, the contribution of different planting rows toward crop physiology and yield is elusive. In addition, the influence of N fertilization on the physiology, yield, and soil water storage of rainfed intercropping systems is poorly understood; therefore, the objective of this experiment was to study the contribution of different crop rows on the physiological, yield, and related traits of wheat/maize relay-strip intercropping (RSI) with and with-out N application. The treatments comprised of two factors viz. intercropping with three levels (sole wheat, sole maize, and RSI) and two N application rates, with and without N application. Results showed that RSI significantly improved the land use efficiency and grain yield of both crops under rainfed conditions. Intercropping with N application (+N treatment) resulted in the highest wheat grain yield with 70.37 and 52.78% increase as compared with monoculture and without N application in 2019 and 2020, respectively, where border rows (BRs) contributed the maximum followed by second rows. The increase in grain yield was attributed to higher values of the number of ears (10-25.33% more in comparison to sole crop without N application) during both study years. The sole wheat crop without any N application recorded the least values for all yield-related parameters. Despite the absence of significant differences, the relative decrease in intercropped maize under both N treatments was over 9% compared to the sole maize crop, which was mainly ascribed to the border rows (24.65% decrease compared to the sole crop) that recorded 12 and 13% decrease in kernel number and thousand-grain weight, respectively than the sole crop. This might be attributed to the reduced photosynthesis and chlorophyll pigmentation in RSI maize crop during the blended growth period. In a nutshell, it can be concluded that wheat/maize RSI significantly improved the land use efficiency and the total yield compared to the sole crops’ yield in arid areas in which yield advantages were mainly ascribed to the improvement in wheat yield.